The principle of insignificance in criminal law (Revista do Tribunal Regional Federal da 3ª Região, 2010)
1. General; 2. Value in law and the legal good; 3. The values and criminal goods protected; 4. Criminal policy in the face of values; 5. The crime and the principle of insignificance; 6. The principle of insignificance as a depreciating value; 7. Insignificance in current doctrine; 8. Paradigms of application of the principle of insignificance; 9. The principle of insignificance in the courts; 10. Conclusions.
Keywords: criminal policy; protected criminal assets; principle of insignificance